Articuler un « penser global » et un « agir local » : la territorialisation des « Community Supported Agriculture » - Michaël Pouzenc (Développement Durable et Territoires)
The increase of “Community Supported Agriculture” (CSA) and their variants is observed all over the world, from concerns formulated everywhere in very similar terms: to look for a healthy diet, to promote an environment-friendly farming, to favor the relocation of the economy… These reflections about proximity relationships between producers and consumers lean widely on a sharing of experiences spread in a much globalized way, valuing a direct relationship from local to global. However, observations carried out locally in France and Mexico combined with a review of the literature, a cartographic analysis of the CSA in Europe and an analysis of their websites allow to see that this relationship from the local to the global comes in interaction and not in replacement of a multi-scalar territorialization, enlightening one aspect of the supposed convergence between the greening of practices and the territorialization of activities, namely the interplay of geographical scales that this convergence implies.